Freedom of association (Trade Union) and its implication on the constitutional guarantee / Ghazali Nik Taib - Nik Taib, Ghazali (Faculty of Law, 1987)
Anyone who surveys the history and structure of labour law must become aware of the inherent tension between the social' demands of the employment relationship and the spirit and possibilities of the law. The evolution of an orderly and, compared with many other countries, even today, reasonably well—functioning system of labour relations, was one of the great achievements of our civilisation. The system of collective bargaining rests on a balance of the collective forces of management and organised labour. To maintain it has on the whole been the poiicy of the legislature during the last twenty years or so. The welfare of the nation has depended on its continuity and growing; strength.